CD49f‐Positive Testicular Cells in Saanen Dairy Goat Were Identified as Spermatogonia‐Like Cells by miRNA Profiling Analysis. Issue 10 (October 2014) - Wu, Jiang; Liao, Mingzhi; Zhu, Haijing; Kang, Kai; Mu, Hailong; Song, Wencong; Niu, Zhiwei; He, Xin; Bai, Chunling; Li, Guangpeng; Li, Xinping; Hua, Jinlian
ABSTRACT miRNAs, a type of small RNA, play critical roles in mammalian spermatogenesis. Spermatogonia are the foundation of spermatogenesis and are valuable for the study of spermatogenesis. However, the expression profiling of the miRNAs in spermatogonia of dairy goats remains unclear. CD49f has been one of the surface markers used for spermatogonia enrichment by magnetic activated cell sorting (MACS). Therefore, we used a CD49f microbead antibody to purify CD49f‐positive and ‐negative cells of dairy goat testicular cells by MACS and then analysed the miRNA expression in these cells in depth using Illumina sequencing technology. The results of miRNA expression profiling in purified CD49f‐positive and ‐negative testicular cells showed that 933 miRNAs were upregulated in CD49f‐positive cells and 916 miRNAs were upregulated in CD49f‐negative cells with a twofold increase, respectively; several miRNAs and marker genes specific for spermatogonial stem cells (SSCs) in testis had a higher expression level in CD49f‐positive testicular cells, including miR‐221, miR‐23a, miR‐29b, miR‐24, miR‐29a, miR‐199b, miR‐199a, miR‐27a, and miR‐21 and CD90, Gfra1, and Plzf. The bioinformatics analysis of differently expressed miRNAs indicated that the target genes of these miRNAs in CD49f‐positive cells were involved in cell‐cycle biological processes and the cell‐cycle KEGG pathway. In conclusion, our comparative miRNAome data provide useful miRNA profiling data of dairy goat spermatogonia cells and suggest that CD49f could be used to enrich dairy goat spermatogonia‐like cells, including SSCs. J. Cell. Biochem. 115: 1712–1723, 2014. © 2014 Wiley Periodicals, Inc.